349 Safety of the Sitting Cervical Position for Elective Spine Surgery. (August 2016) - Sandwell, Stephen; Kimmell, Kristopher T.; Silberstein, Howard J.; Rodenhouse, Thomas G.; Maurer, Paul K.; Pilcher, Webster H.; Walter, Kevin A.
Abstract : INTRODUCTION: The sitting cervical position affords advantages over prone positioning for elective posterior cervical decompression and fusion. A potential disadvantage is the risk for venous air embolism. METHODS: We retrospectively identified all adult elective posterior cervical surgeries at our institution between 2009 and January 2014. Using International Classification of Diseases, Ninth Revision coding, we searched for incidences of air embolism, myocardial infarction, pulmonary embolism, and deep vein thrombosis. Operative time, estimated blood loss, and case type distribution were also recorded. Surgeries for trauma, tumor, or that involved the occipital-cervical junction were excluded. RESULTS: Between 2009 and January 2014, 560 surgeries were performed in the sitting cervical position and 20 in the prone position. No venous air embolisms were reported for either group. The average surgical time was 1 hour 46 minutes for prone-positioned patients and 1 hour 25 minutes for surgeries in the sitting position ( P = .003). Thirty-day perioperative complications among the sitting-position patients included 2 myocardial infarctions, 1 pulmonary embolism attributed to venous thrombosis, and 2 deep venous thromboses, for a total cardiovascular complication rate of 0.9%. CONCLUSION: Our study adds to the literature supporting the safety of the sitting cervical position. The sitting position is preferred by many surgeons at our institution. It provides a dry surgical field, easily verified spinal alignment prior to fusion, and superior visualization on intraoperative x-rays due to reduced shoulder artifact. Furthermore, our data suggest that operative times may be shorter. Although the risk of venous air embolism exists, clinically significant occurrences are extremely rare. Given our large volume of surgeries in the sitting position, we believe the advantages outweigh the risks.